Increased number of teeth predict acquisition of mutans streptococci in infants. (3rd September 2014) - Nelson, Suchitra; Albert, Jeffery M.; Soderling, Eva; Malik, Anchal; Curtan, Shelley; Geng, Cuiyu; Milgrom, Peter
<x xml:space="preserve">Abstract</x> This longitudinal study of 194 very‐low birthweight (VLBW) and 184 normal birthweight (NBW) infants hypothesized that the causal pathway between birth group (VLBW or NBW) and mutans streptococci (MS) acquisition (presence) at 18–20 months is mediated by biological, behavioral, and caregiver MS levels. Biological (number of teeth at 8 and 18–20 months and enamel hypoplasia) and behavioral (brushing/cleaning, sweet snacks, breastfeeding, and dental access) factors were assessed using dental examinations and caregiver questionnaire responses at 8 and 18–20 months. Infant MS acquisition and caregiver MS levels were assessed from saliva and plaque samples collected at 8 and 18–20 months. Structural equation modeling evaluated the causal pathway with latent variables for biology and behavior. Mutans streptococci presence was similar between birth groups at 18–20 months (40% in VLBW infants and 49% in NBW infants), but was significantly higher for NBW infants at 8 months. Increased number of teeth at 8 and 18–20 months was associated with biological risk. Infants whose caregivers had a 1‐point higher score on MS had a significantly (1.5) higher odds of MS presence. Caregiver behavior was not associated with MS presence. Early‐intervention efforts should focus on delaying initial acquisition and improving caregiver awareness of taking care of erupting primary teeth.